2021
DOI: 10.1007/s00247-021-05132-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid-lymphatic fistula causing spontaneous intracranial hypotension in a child with kaposiform lymphangiomatosis

Abstract: Spontaneous intracranial hypotension is an uncommon etiology of secondary headaches in children. We report a unique case of a girl with kaposiform lymphangiomatosis who developed postural headaches and imaging features of spontaneous intracranial hypotension without a spinal extradural collection. The girl underwent dynamic computed tomography myelography which revealed a cerebrospinal fluid (CSF)-lymphatic fistula related to a lymphatic malformation associated with the right T10 nerve. She underwent surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Biomarkers have been identified, especially serum angiopoietin‐2 (Ang‐2) levels, which are elevated 21,22 . Other rare symptoms include pseudotumor cerebri, which may be due to blockage of venous return in the neck by lymphangiomatous tissue, and cerebrospinal fluid (CSF)‐lymphatic fistula causing spontaneous intracranial hypotension 23,24 . The complex and diverse nature of presenting symptoms, along with the lack of familiarity of clinicians with this rare disorder, frequently results in the misdiagnosis of KLA as pneumonia, cancer, bone marrow failure, or other vascular anomalies, sometimes leading to years of diagnostic uncertainty and delays in effective treatment.…”
Section: Clinical Presentation and Imagingmentioning
confidence: 99%
“…Biomarkers have been identified, especially serum angiopoietin‐2 (Ang‐2) levels, which are elevated 21,22 . Other rare symptoms include pseudotumor cerebri, which may be due to blockage of venous return in the neck by lymphangiomatous tissue, and cerebrospinal fluid (CSF)‐lymphatic fistula causing spontaneous intracranial hypotension 23,24 . The complex and diverse nature of presenting symptoms, along with the lack of familiarity of clinicians with this rare disorder, frequently results in the misdiagnosis of KLA as pneumonia, cancer, bone marrow failure, or other vascular anomalies, sometimes leading to years of diagnostic uncertainty and delays in effective treatment.…”
Section: Clinical Presentation and Imagingmentioning
confidence: 99%
“…Recently, Yokoi et al [ 6 ] reported a case of a child with GDS and CSF leak into osteolytic posterior bony elements Th9-10, treated with direct surgical repair and vertebral fixation. Soderlund et al [ 4 ] presented a case of a child with KLA who developed postural headaches due to a CSF-lymphatic fistula related to a lymphatic malformation associated with the right Th10 root nerve. In this case, the surgical ligation of the CSF-lymphatic fistula was undertaken, resulting in the resolution of the headache.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not experience any difficulty repositioning patients on the foam wedge, alternative means of elevating the patient's pelvis without requiring movement on the CT table, such as placing an inflatable mattress (HoverMatt; HoverTech International) under the patient's hips and inflating it transiently after the intrathecal injection of contrast, might represent further refinements to the technique. 16…”
Section: Discussionmentioning
confidence: 99%